Study of Burger Equation Using q-HAM with Yang-Abdel-Cattani Derivative (Contemporary Mathematics, 2025)
In order to solve the generalized Burgers equation, this research work introduces one of the most recent operators in fractional calculus. An easier-to-understand version of the problem can be obtained by using the Yang-Abdel-Cattani fractional operator. The generalized Burgers equation's result is obtained analytically effectively using the q-homotopy analysis method (q-HAM). A visual study is also acquired to demonstrate the operation of the technique. By employing this approach to solve the generalized Burgers problem, this study advances the field of nonlinear differential equations.
Keywords: Burger equation; Yang-Abdel-Cattani derivative; fractional operator; fixed point condition; homotopy; q-homotopy; q-HAM; HAM